Brain Histology and Immunohistochemistry After Resuscitation From Hemorrhagic Shock in Swine With Pre-Existing Atherosclerosis and Sodium Thiosulfate (Na2S2O3) Treatment - Denoix, Nicole; McCook, Oscar; Scheuerle, Angelika; Kapapa, Thomas; Hoffmann, Andrea; Gündel, Harald; Waller, Christiane; Szabo, Csaba; Radermacher, Peter; Merz, Tamara (Frontiers in Medicine, 2022)
Background: The hydrogen sulfide (H2S) and the oxytocin/oxytocin receptor (OT/OTR) systems interact in the central nervous and cardiovascular system. As a consequence of osmotic balance stress, H2S stimulates OT release from the paraventricular nuclei (PVN) in the hypothalamic regulation of blood volume and pressure. Hemorrhagic shock (HS) represents one of the most pronounced acute changes in blood volume, which, moreover, may cause at least transient brain tissue hypoxia. Atherosclerosis is associated with reduced vascular expression of the main endogenous H2S producing enzyme cystathionine-γ-lyase (CSE), and, hence, exogenous H2S administration could be beneficial in these patients, in particular after HS. However, so far cerebral effects of systemic H2S administration are poorly understood. Having previously shown lung-protective effects of therapeutic Na2S2O3 administration in a clinically relevant, long-term, porcine model of HS and resuscitation we evaluated if these protective effects were extended to the brain. Methods: In this study, available unanalyzed paraffin embedded brain sections (Na2S2O3 N=8 or vehicle N=5) of our recently published HS study were analyzed via neuro-histopathology and immunohistochemistry for the endogenous H2S producing enzymes, OT, OTR, and markers for brain injury and oxidative stress (glial fibrillary acidic protein (GFAP) and nitrotyrosine). Results: Neuro-histopathological analysis revealed uninjured brain tissue with minor white matter edema. Protein quantification in the hypothalamic PVN showed no significant inter-group differences between vehicle or Na2S2O3 treatment. Conclusions: The endogenous H2S enzymes, OT/OTR co-localized in magnocellular neurons in the hypothalamus, which may reflect their interaction in response to HS-induced hypovolemia. The preserved blood brain barrier (BBB) may have resulted in impermeability for Na2S2O3 and no inter-group differences in the PVN. Nonetheless, our results do not preclude that Na2S2O3 could have a therapeutic benefit in the brain in an injury that disrupts the BBB, e.g. traumatic brain injury (TBI) or acute subdural hematoma (ASDH).